Multi-Objective Variational Autoencoder for Blockchain Forensics: Detecting and Attributing Lazarus APT Group Wallets - Kucuk, Duzgun; Ertam, Fatih (Institute of Electrical and Electronics Engineers Inc., 2025)
The exponential growth of blockchain-based financial crimes necessitates advanced analytical frameworks capable of distinguishing between legitimate and illicit cryptocurrency activities. This paper presents a deep learning architecture based on an Advanced Variational Autoencoder (VAE) with multi-objective learning for Ethereum wallet classification. The model is trained on 116 behavioral indicators capturing graph topology, temporal dynamics, and transaction flow characteristics. The architecture integrates self-attention mechanisms, residual connections, and a dual-objective loss combining reconstruction and classification. Trained on a balanced dataset of 15260 Ethereum wallets (7603 Lazarus; 7657 non-Lazarus), the model achieves 98.998% accuracy, 99.128% precision, 98.862% recall, and 99.947% AUC. The non-Lazarus cohort includes 3930 normal/licit, 202 mixer, 1141 nested-service, and 2384 bridge users, of which 940 are identified as illicit. Mixer and nested-service users are treated as illicit but non-Lazarus, while the remaining bridge users are considered behavioral. The framework captures complex temporal patterns, cross-chain bridge interactions, gas optimization strategies, and network-topology characteristics that distinguish Lazarus-linked operations from non-Lazarus transactions. The main contributions are: an enhanced VAE jointly optimized for reconstruction and classification, an analysis of key architectural choices, and an interpretable framework enabling forensic insight. The 116 features are organized into 18 thematic categories covering structural, temporal, value-flow, service-specific, and behavioral signals. © 2025 IEEE.
18th International Conference on Information Security and Cryptology, ISCTurkiye 2025 -- 22 October 2025 through 23 October 2025 -- Ankara -- 215330
Keywords: blockchain forensics; cryptocurrency; cyber threat intelligence; Lazarus APT; money laundering detection; multi-objective learning; variational autoencoder